The Use of Guided Imagery in Family of Origin Group Therapy - Paré, Timothy J.; Shannon-Brady, Dustin T. (Canadian Journal of Counselling and Psychotherapy, 1996)
This paper describes the use of guided imagery in a family of origin group. The group isdesigned to facilitate the process of differentiation from family. Awareness is identified as thekey "ingredient" that contributes to the developmental task of differentiation. The paperoutlines three stages in the process of differentiation from family; identification, integrationand activation of the individual's thoughts, feelings and behaviours. The use of guided imageryishighlighted as a means for accessing the unconscious and increasing the clients' awareness offamily issues and promoting self-differentiation. Specific examples of guided imagery for familyof origin work and an innovative use of the genogram are provided.